2021
DOI: 10.1149/10101.0173ecst
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Behavior of Titanium Alloys Using Potentiodynamic Polarization

Abstract: Titanium is for aerospace production is of 80%. In an aircraft structure, 15% of the weight is titanium. The principal reasons to use titanium alloys are the save of weight, increase performance temperatures ratio and corrosion resistance. To analysed corrosion behavior of Ti alloys, polarization potentiodynamic cyclic was employed. Electrolytes used were H2SO4 and NaCl at 3.5% wt. The type of corrosion presented in Ti alloys was generalized in both electrolytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Several surface modification methods, including electrochemical passivation, thermal oxidation, and plasma electrolytic oxidation, as well as the electrochemical characteristics of the produced layers (mainly consisted of TiO2) on Ti-6Al-4V and β-Ti alloys, are introduced [97, [167][168][169][170][171][172]. As summarized in Ta- Jaquez et al [164,165] studied the behavior of titanium alloys (Cp-Ti, Ti-6Al-2Sn-4Zr-2Mo, and Ti-6Al-4V) in the presence of acid solutions and Hank's through potentiodynamic polarization and electrochemical noise. Statistical methods indicated that the passive layer created on Ti alloys surfaces is unstable; this condition is notable for Ti-6Al-2Sn-4Zr-2Mo in NaCl solution.…”
Section: Outlook and Future Perspectivesmentioning
confidence: 99%
“…Several surface modification methods, including electrochemical passivation, thermal oxidation, and plasma electrolytic oxidation, as well as the electrochemical characteristics of the produced layers (mainly consisted of TiO2) on Ti-6Al-4V and β-Ti alloys, are introduced [97, [167][168][169][170][171][172]. As summarized in Ta- Jaquez et al [164,165] studied the behavior of titanium alloys (Cp-Ti, Ti-6Al-2Sn-4Zr-2Mo, and Ti-6Al-4V) in the presence of acid solutions and Hank's through potentiodynamic polarization and electrochemical noise. Statistical methods indicated that the passive layer created on Ti alloys surfaces is unstable; this condition is notable for Ti-6Al-2Sn-4Zr-2Mo in NaCl solution.…”
Section: Outlook and Future Perspectivesmentioning
confidence: 99%
“…Pseudopassivation is related to a non-stable anodized due to a higher presence of other alloy elements (vanadium, molybdenum, or chromium). As atomic distances are higher than in a pure TiO 2 layer, Clions can attack and dissolve the passive layer through interstitial penetration (13)(14)(15). Nevertheless, the alloy presented the higher Ecorr (0.15 V) and the lower Icorr (9.12×10 -9 A/cm 2 ), indicating that corrosion kinetic will be slower than the other anodizes.…”
Section: Chemical Compositionmentioning
confidence: 99%
“…These structure–function relationships are not well-established for AM parts. Some work has been published describing the microstructure and mechanical properties of SLM-processed Ti-5553. ,, However, there is little published research regarding the electrochemical characterization of SLM or die cast Ti-5553. , To address this knowledge gap, we report herein on the material characterization and electrochemical properties of SLM-prepared Ti-5553 specimens as-processed (i.e., with their native surface roughness and oxide film) and after abrading and polishing to smooth the surface texture, thereby reducing the surface roughness and enabling the formation of a less defective and more compact oxide film.…”
Section: Introductionmentioning
confidence: 99%